MOBILE LEARNING: CONTEXT ADAPTATION AND SCENARIO APPROACH - Vladimir V. Kureichik; Sergey I. Rodzin; Lada S. Rodzina (Открытое образование (Москва))
The paper proposes a model of an open architecture for component context-dependent systems of computer training to the needs of the software applications of intelligent learning environments and adaptive learning systems. The structure of a content management system is developed based on Semantic Web. The model for developing of the engine is supposed to be based on probabilistic automata. Another part of work is developing of learning scenarios and possibilities for its adaptation. The context approach for personalization of learning style is described in the paper as well.